Comparison of Diversion and Restorative Justice in Handling Juvenile Crimes within Indonesia's Criminal Justice System - Rustam, Rustam; Wibawa, Iskandar (Jurnal Indonesia Sosial Sains, 2025)
The Juvenile Criminal Justice System in Indonesia prioritizes an approach that educates and rehabilitates children who are facing the law. Restorative approaches, such as diversion and restorative justice, have become very relevant to achieve these goals. This study aims to examine legal protection for the application of restorative justice in handling juvenile crimes and understand diversion and restorative justice as a mechanism for resolving criminal acts outside the formal criminal justice process. This study uses a non-doctrinal method with qualitative descriptive analysis. The data used is sourced from primary, secondary, and tertiary legal documents. The results of the study show that diversion functions as a transfer of the settlement of children's cases from the formal criminal justice process to a mechanism outside the judiciary. This provides opportunities for children to improve themselves and avoid negative stigma due to formal justice. Meanwhile, restorative justice involves all parties affected by criminal acts with the aim of repairing damaged relationships, recovering losses, and preventing the recurrence of criminal acts. Thus, concluding a restorative approach both through diversion and restorative justice is effective in creating a more humane child penal system. This approach can focus on victim recovery and also provide child rehabilitation to perpetrators of crimes to ensure the sustainability of social recovery.